2021
DOI: 10.46575/agrihumanis.v2i1.97
|View full text |Cite
|
Sign up to set email alerts
|

Kelimpahan Relatif Artropoda Predator Penghuni Tajuk Tanaman Padi Galur Padi Rakitan Politeknik Negeri Lampung

Abstract: The abundance of predatory arthropods in the rice field ecosystem acts as a biological agent that suppresses pest populations. This study aims to analyze the types of species, individuals, and abundance of predatory arthropods. The research was conducted at the Lampung State Polytechnic Seed Teaching Farm in August-December 2020. The rice plant lines planted by Lampung State Polytechnic were 14 New Type Rice (PTB) lines, namely Pandan Wangi (PW, B1, B2, B3, B4, B7, D2, D3, F3, F4, H1, H4, K, and L2 with 2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
0
0
1
Order By: Relevance
“…Result showed that spiders from the Tetragnathidae family are more abundant in comparison with spiders from the Oxyopidae and Lycosidae families. This is in line with research [20,21,22] whereas many spiders from the Oxyopidae, Tetragnathidae and Lycosidae families found in the rice plants during the growth period, both vegetative and generative phase. Spiders from the Tetragnathidae family are often found by making a net.…”
Section: Resultssupporting
confidence: 90%
“…Result showed that spiders from the Tetragnathidae family are more abundant in comparison with spiders from the Oxyopidae and Lycosidae families. This is in line with research [20,21,22] whereas many spiders from the Oxyopidae, Tetragnathidae and Lycosidae families found in the rice plants during the growth period, both vegetative and generative phase. Spiders from the Tetragnathidae family are often found by making a net.…”
Section: Resultssupporting
confidence: 90%
“…Keywords: Pests, Diseases, Rice Lines PENDAHULUAN Padi merupakan komoditi pangan utama yang dibudidayakan hampir sebagian besar petani Indonesia (Siregar et al, 2021) Faktor pembatas peningkatan produksi padi salah satunya adalah tingkat serangan hama dan penyakit yang menyerang varietas padi yang dibudidayakan (Budiarti et al, 2021a;Budiarti et al, 2021b)…”
unclassified